Telomere shortening in hypertensive heart disease depends on NOX2-mediated loss of PRDX1 and oxidative DNA damage. (3rd October 2022) - Brandt, M; Khraisat, S; Doerschmann, H; Kalinovic, S; Molitor, M; Karbach, S H; Daiber, A; Munzel, T; Wenzel, P
Abstract: Background: Heart failure (HF) coincides with cardiomyocyte telomere shortening. Arterial hypertension is the most prominent risk factor for HF. Both HF and arterial hypertension are associated with dysregulation of the neurohormonal axis and increased ROS. However, how neurohormonal activation is linked to telomere shortening in the pathogenesis of HF is incompletely understood. Further, recent findings suggest that peroxiredoxin 1 (PRDX1) can act as a telomere specific antioxidant. Methods: To induce hypertensive HF, male C57BL/6J mice were subjected to AngII-infusion, uninephrectomy and high-salt (AngII++) for 5 weeks. Cardiac function was assessed by ultrasound. Mouse adult cardiomocytes (CMs) isolated from C57BL/6J mice and mice lacking the NADPH-oxidase (NOX) 2/gp91phox as well as rat ventricular CM-derived cells (H9C2) were stimulated with AngII. Telomere length was quantified by Q-FISH after staining with a C-rich telomere probe (TelC). DNA/RNA-damage was evaluated after staining for Oxo-8-Gua (8-oxo-7, 8-dihydroguanine) and Oxo-8-G (8-oxo-7, 8-dihydroguanosine). Superoxide (O2-) was quantified by 2-hydroxyethidium (2-HE) using HPLC analysis. Colocalization of Oxo-8-Gua and TelC was quantified by automated image analysis. (Sub)cellular and tissue expression of gp91phox/Nox2 and PRDX1 was evaluated by ICC/IHC. All image quantification was conducted semiautomatically. Results: In mice subjected to hypertensive HF, CM telomere shortening correlated significantly with both left ventricular (LV) dilatation and impairment of LV systolic function, paralleled by a significant loss of myocardial PRDX1 and significantly increased myocardial DNA/RNA-damage. Similarly, CMs stimulated with AngII exhibited significant telomere shortening, significant loss of PRDX1 and significantly increased DNA/RNA-damage, together with significantly increased CM superoxide production and significantly increased expression of the superoxide generating enzyme gp91phox/NOX2. Correspondingly, deficiency of gp91phox/NOX2 significantly prevented AngII-induced CM telomere shortening, DNA/RNA-damage and PRDX1-depletion. A similar effect could be observed upon stimulation of CMs with the specific histone deacetylase (HDAC) 6-inhibitor tubastatin, which prevents deacetylation of PRDX1. Conclusion: We could provide first evidence that in heart failure, ROS originating from increased NOX2-activity leads to depletion of the telomere-targeted antioxidant and repair-protein PRDX1, which results in damage to the telomeric DNA. Both depletion of NOX2 as well as harnessing the intrinsic antioxidant defense by stabilizing PRDX1 via HDAC6-inhibition prevented CM telomere shortening and could be further evaluated as potential therapeutic targets to address heart failure. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Federal Ministry for Education and Research